Assessment of Pregelatinized Corn Starch (Zea mays L.) as an Excipient in Pharmaceutical Preparations - Siswanto, Agus; Hartati, Dita Nur Hartati; Qiptiah, Deva Aldina Maria Qiptiah; Rahayu, Wiranti Sri Rahayu; Suparman, Suparman (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Indonesia has a large potential for corn starch production since corn is one of the most widely grown foodstuffs. In addition to being a food ingredient, corn also has the potential as an excipient in pharmaceutical preparations because of its very high starch content, which is 72-73% of the total weight. In tablet preparations, starch is widely used as a binder, disintegrant, and filler. One of the weaknesses of starch is its poor mechanical properties. Pregelatinization is one of the physical modification methods that can improve the mechanical properties of corn starch. The purpose of this study was to determine the effect of pregelatinized corn starch on the physical, chemical, and mechanical properties. Pregelatinized corn starch was prepared as follows: 250 g of starch was added to 250 mL of distilled water, heated at 70°C for 20 minutes, stirred until thick, dried in a drying cabinet at 60°C for 24 hours, and sieved through a 16/18 mesh sieve. The starch was tested for its physical, chemical, and mechanical properties. The results showed that the pregelatinized corn starch base on physical, microscopic and functional properties better than native corn starch in the formulation composition or process.